Challenges New Science Teachers Face - Davis, Elizabeth A.; Petish, Debra; Smithey, Julie (Review of Educational Research, 2006)
Providing support focused on real challenges is critical in retaining highly qualified new science teachers, but the field lacks a systematic description of these teachers’ needs. The authors of this article examine the areas that science teachers are expected to understand: (1) the content and disciplines of science, (2) learners, (3) instruction, (4) learning environments, and (5) professionalism. They review the literature on challenges facing preservice and early-career science teachers, identify issues on which conventional wisdom is supported or called into question, and highlight the areas where the existing research is inadequate as a basis for generalization. For example, the authors found few studies on how new science teachers use curriculum materials or how they understand scientific inquiry. Their overview of challenges is followed by a discussion of how these teachers can be supported.
Keywords: Science Teachers; new teachers; teaching challenges